Validity and reliability of an eight antennae ultra-wideband local positioning system to measure performance in an indoor environment - Pino-Ortega, J.; Bastida-Castillo, A.; Gómez-Carmona, C. D.; Rico-González, M. (Sports Biomechanics, 2024)
Validity and reliability have become crucial factors in tracking player load and positioning. One of the most important parameters to guarantee accurate measurements with radiofrequency systems is the number of reference nodes used to calculate player position. However, the accuracy of ultra-wideband (UWB) technology has only been analysed with 6 antennae. So, the purpose of the present study was to analyse the accuracy and inter-unit reliability of an UWB system with eight antennae. Three well-trained males covered 18 trajectories for the analysis of x- and y- coordinate accuracy assessment related to the positional variation among eight antennae UWB data and lines on a basketball court. This was achieved using geographical information system mapping software that calculated, for each interval and participant, the distance from the main axis of locomotion and the opposite side of the field every 0.5 s. The results showed that this is a valid system (Mean=0.03 m; magnitude differences=0.21% with real measures as reference; %CV <1% in all cases) for measuring locomotion and positioning. Besides, the inter-unit, test-retest and inter-subject analysis did not influence the reliability results. So, an eight antennae UWB system can be considered suitable for locomotion and positioning in an indoor environment.